Accumulation of Thorium and/or Uranium using Various Microbes - T. Tsurata (International Mineral Processing Congress, 2014)
The accumulation of thorium and/or uranium by various microorganisms from a solution containing thorium and/or uranium at pH 3.5 was examined. Among the species tested, a high accumulation ability for thorium was exhibited by strains of gram-positive bacteria, such as Bacillus megaterium, B. subtilis, Micrococcus luteus, Rhodococcus erythropolis, and actinomycetes, such as Streptomyces levoris. On the other hand, though uranium was accumulated in small amounts from the solution containing both elements by all these microorganisms, actinomycetes, such as S. flavoviridis and S. levoris had relatively high uranium accumulation abilities. In these high performance thorium- and uranium- accumulating microorganisms, S.levoris, which accumulated the largest amount of uranium from the solution containing only uranium at pH 3.5, could accumulate about 300 µmol thorium and 133 µmol uranium per gram dry wt. of microbial cells from a solution containing both thorium and uranium at pH 3.5. After this screening, uranium accumulation using microorganisms isolated from uranium mines, among which some strains of bacteria were found to possess an extremely high uranium accumulating ability. The microbial biomass may thus be considered for use as an accumulating agent for the removal and recovery of uranium that may be present in metallurgical effluents, mine tailings, seawater and other sources. Recently, hundreds of micro-organisms existing in uranium deposits located in North America, Australia, and Japan for their ability to accumulate large amounts of uranium, and found some new strains which accumulated large amounts of uranium, such as Lactobacillus and Bacillus sp. from Japanese and Arthrobacter and Bacillus sp. from the United States uranium deposits. These bacterial strains can accumulate about 2500 µmol uranium per gram dry wt. of microbial cells within one hour. These microbial cells can remove uranium from the uranium refining wastewater with a high efficiency. The accumulation of uranium from a solution (pH 5.8) by microorganisms contained Arthrobacter nicotianee, which is a similar strain mentioned above Arthrobacter sp., was examined. Among the 76 strains of 69 species tested (23 bacteria, 20 actinomycetes, 18 fungi, and 15 yeasts), high uranium accumulation ability was exhibited by strains of the bacteria, A. nicotianae, B. subtilis, and M. luteus. A. nicotianae cells, which showed the best performance, could accumulate about 698 mg uranium (2.58 mmol) per gram dry wt. of microbial cells.